Islamistisk maskulinitet og muslimske maskuliniteter - Gerami, Shahin (Kvinder, Køn & Forskning, 2005)
A core component of the ideology of the Islamic Revolution was reformulation of gender discourse around an Islamic hypermasculinity that produced/ promoted three ideals of manhood: Mullahs who are the interpreters of the quran and shari’at; martyrs, the young men who abide the dictates of the mullahs and sacrifice themselves for the republic; and ordinary men, who are perceived to have benefited from this hypermasculinity. It is argued that economic hardship and socio-political pressure assail all men. Also, they pay for gender discrimination against women in general and women of their own social group in particular.